2013
DOI: 10.1016/j.virol.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro functional analyses of the human immunodeficiency virus type 1 (HIV-1) integrase mutants give new insights into the intasome assembly

Abstract: A functional study of mutants of the human immunodeficiency virus type 1 (HIV-1) integrase (IN) was conducted with the support of a recently proposed HIV-1 intasome model. Firstly, we investigated the predicted position of the C-terminal domain (CTD) and the flexibility of the alpha-6 helix by mutating the residue Ile-203. This had no impact on the 3'-processing reaction but reduced the strand transfer reaction and the formation of tetramers. Secondly, the residues Ile-141 of the catalytic loop and Glu-246 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Likewise, the flexible finger-loop has also been implicated in viral infectivity and IN functional tetramerization, nuclear localization, enzymatic activity and conformational rearrangement of IN upon DNA binding (Berthoux et al, 2007; Cellier et al, 2013; Hare et al, 2009a; Zhao et al, 2008). For example, K186 of the finger-loop has been shown to stabilize the tetrameric form of IN via a salt-bridge formed with the NTD E11 from the adjacent dimer (Berthoux et al, 2007; Hare et al, 2009a), and I191 has been proposed to support a crucial hydrophobic core at the dimer-dimer interface during tetramer formation.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the flexible finger-loop has also been implicated in viral infectivity and IN functional tetramerization, nuclear localization, enzymatic activity and conformational rearrangement of IN upon DNA binding (Berthoux et al, 2007; Cellier et al, 2013; Hare et al, 2009a; Zhao et al, 2008). For example, K186 of the finger-loop has been shown to stabilize the tetrameric form of IN via a salt-bridge formed with the NTD E11 from the adjacent dimer (Berthoux et al, 2007; Hare et al, 2009a), and I191 has been proposed to support a crucial hydrophobic core at the dimer-dimer interface during tetramer formation.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of peptide to bind CCDCTD, which possesses an exposed site-1 but blocked site-2, indicates that site-2, which docks the CTD during multimerization, is a preferred binding site. CTD involvement in the multimerization of IN is well documented (reviewed in (23)), and the relative orientation of the CTD with regard to the CCD has previously been implicated in functional IN assembly (29). Moreover, analysis of available CCD structures bound to small molecules at site-2 reveals a pocket that forms upon binding, which displaces the flexible N-terminus of α4, a displacement that would also interfere with and inhibit the binding of viral DNA and IN catalytic activity ( Figure 4D).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the form of these smaller-multimeric IN entities, likely dimers, and their interaction interfaces and assembly pathways are yet to be defined, we suggest that the residue at the C-terminal tip of CCD a-5 (F187 in FIV) may pin the dimer interface, which hinges the two protomers together during flexible IN rearrangements upon DNA binding. Such a pivot at resi- (Berthoux et al, 2007;Cellier et al, 2013;Hare et al, 2009a).…”
Section: The Catalytic Loop Is Fully Structured In a ''Closed'' Confomentioning
confidence: 99%
“…This is probably because, in addition to practicality and convenience in construct preparations (Jaskolski et al, 2009), the region linking the CCD to CTD (C-terminal linker [CTL]) was found, unlike the NTD and CTD, to function in cis to the CCD (Engelman et al, 1993;Shibagaki et al, 1997). Functional importance of residue composition, and finger flexibility, of the CTL region (186-196 from HIV-1 IN) has been implicated in viral infectivity and in IN functional tetramerization, nuclear localization, enzymatic activities, and conformational changes upon DNA binding (Berthoux et al, 2007;Cellier et al, 2013;Hare et al, 2009a;Zhao et al, 2008). Still, if the CTL plays a crucial role in the formation of IN dimers, the precursors of functional tetramers, it remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation